Bubble columns operated under industrially relevant conditions – Current understanding of design parameters. (14th April 2015) - Rollbusch, Philipp; Bothe, Melanie; Becker, Marc; Ludwig, Martina; Grünewald, Marcus; Schlüter, Michael; Franke, Robert
Abstract: Despite the fact that bubble columns are widely established within the process industry as multiphase reactors and gas–liquid contactors, common research has been focused on the description of bubble column hydrodynamics under atmospheric conditions. Industrial production is usually conducted at pressures above atmospheric and temperatures above ambient in processes primarily involving the use of organic solvents. Because hydrodynamic parameters such as gas holdup and backmixing determine the necessary reactor design and impact reactor performance, detailed knowledge of these variables is crucial for optimal design and operation of bubble column reactors. The purpose of this article is to give an overview of research studies that deal with bubble column hydrodynamics at elevated pressures. A recommendation for further research concerning this topic is provided as well.